Proliferation/Quiescence: When to start? Where to stop? What to stock? - Daignan-Fornier Bertrand; Sagot Isabelle (Cell Division, 2011)
Abstract The cell cycle is a tightly controlled series of events that ultimately lead to cell division. The literature deciphering the molecular processes involved in regulating the consecutive cell cycle steps is colossal. By contrast, much less is known about non-dividing cellular states, even if they concern the vast majority of cells, from prokaryotes to multi-cellular organisms. Indeed, cells decide to enter the division cycle only if conditions are favourable. Otherwise they may enter quiescence, a reversible non-dividing cellular state. Recent studies in yeast have shed new light on the transition between proliferation and quiescence, re-questioning the notion of cell cycle commitment. They also indicate a predominant role for cellular metabolic status as a major regulator of quiescence establishment and exit. Additionally, a growing body of evidence indicates that environmental conditions, and notably the availability of various nutrients, by impinging on specific metabolic routes, directly regulate specific cellular re-organization that occurs upon proliferation/quiescence transitions.